Business Plan: Rencana Pendirian Kedai Teh di Jakarta Barat - Leonita Wijaya; Eddy Herjanto (Universitas Tarumanagara, 2020)
“Business Plan Opening a Tea Café at Jakarta Barat” is a planning for opening a business which sell tea for take away. With the lifestyle of the community, we can see a potential opportunity to sell drinks which are currently trending among teenagers to young executives. This business plan aims to create a new business plan in the food and beverage industry and create opportunities for profit. Based on the results of the analysis and discussion, it can be concluded that this business is feasible to be realized on the basis of considerations including Porter's Five Forces analysis and SWOT analysis. This business financial planning also shows that this business will provide profit and payback period which is quite short, 1 year 4 months. And the Net Present Value (NPV) value of Rp 440,173,246,- this shows that this investment is very profitable, and the Internal Rate of Return (IRR) value is 266%, which means it is much higher than the interest rate.